Timing for starting second-line therapy in recurrent ovarian cancer. Issue 1 (January 2011) - Guarneri, Valentina; Barbieri, Elena; Dieci, Maria Vittoria; Piacentini, Federico; Conte, PierFranco
Ovarian cancer is the leading cause of gynecologic cancer-related death in Europe and the USA. The optimal treatment strategy for this malignancy includes accurate presurgical and surgical staging, optimal debulking surgery, and first-line therapy with platinum-based chemotherapy. Unfortunately, the majority of patients diagnosed with advanced ovarian cancer will eventually relapse and die. However, an appropriate management can have a major impact on survival: salvage chemotherapy can prolong survival in the majority of cases and, in selected patients, surgical cytoreduction of recurrent disease can be beneficial. The optimal timing for starting second-line therapy should be based on symptomatic or radiologic recurrence. In fact, even though cancer antigen 125 (CA 125) elevation significantly anticipates a clinical relapse, a randomized trial failed to show a survival advantage for starting second-line therapy on the basis of CA 125 elevation. This is the most solid evidence coming from a randomized trial; however, we must take into account some limitations: in this study the role of secondary cytoreduction was not considered and, at the time of study conduction, more active salvage drugs/regimens were not yet available. In the near future, a better knowledge of ovarian cancer biology, more sensitive diagnostic techniques, more accurate and less invasive surgical procedures along with the availability of new agents will further improve prognosis. In this scenario, the anticipation of salvage therapy will probably play a different role.